Impression Communication Management on Organizational Communication: LAZ Coal Case Study - Rahmad Vendi; Harliantara Harliantara; Yenny Yenny; Nurannafi Farni Syam Maella; Zulaikha Zulaikha; Farida Farida (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This case study delves into the significance of impression communication management in influencing organizational communication at LAZ Coal, a prominent coal mining company. The findings provide valuable insights for scholars and practitioners in the fields of organizationalhis research explores the impact of strategic impression communication on stakeholder perceptions, information sharing, and the overall communication environment within an organization. The extensive body of research on impression management emphasizes its importance in projecting a positive organizational image and effectively managing stakeholder perceptions. In the same vein, studies on organizational communication highlight its crucial importance in promoting the sharing of information, teamwork, and the establishment of a unified organizational culture. This case study seeks to combine these two areas to explore how impression communication management and organizational communication interact with each other. This research utilizes a qualitative, multi-method design, following the case study approach proposed by RK Yin. We collected data by conducting in-depth interviews with key personnel, analyzing internal communications documents, and observing organizational interactions. The case study approach provided a thorough understanding of the phenomenon within the LAZ Coal setting, taking into account the context and various factors involved. The findings highlight how LAZ Coal's strategic approach to communication has had a significant impact on both internal and external dynamics. This includes their consistent messaging, selective information dissemination, and effective use of communication channels. As a result, employee engagement, stakeholder perceptions, and the overall communicative culture within the company have been significantly influenced. The case study highlights the significance of incorporating impression communication management into the overall organizational communication strategy. By acknowledging the interdependence of these two areas, LAZ Coal and similar organizations can improve their capacity to present a positive image, promote open information exchange, and foster a cooperative and effective communication environment. The findings provide valuable insights for scholars and practitioners in the fields of organizational communication and strategic management.